Intracellular synthesis of gold nanoparticles using alga tetraselmis kochinensis - Senapati, Satyajyoti; Syed, Asad; Moeez, Sana; Kumar, Ashutosh; Ahmad, Absar (Materials Letters, 2012)
The development of eco-friendly synthesis protocol for the synthesis of nanoscale materials of different compositions, shapes and sizes is an important area of research in the field of nanotechnology. In this paper, we report on the use of alga Tetraselmis kochinensis in the intracellular synthesis of gold nanoparticles of dimensions 5-35 nm. The particles are more concentrated upon the cell wall than on the cytoplasmic membrane, possibly due to reduction of the metal ions by enzymes present in the cell wall and cytoplasmic membrane. These intracellular nanoparticles may have applications in drug delivery, biomedical applications, catalysis, etc. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Algae; Biosynthesis; Nanoparticles; nanotechnology; Tetraselmis kochinensis

Biotransformation of vinblastine to vincristine by the endophytic fungus fusarium oxysporum isolated from catharanthus roseus - Kumar, Ashutosh; Ahmad, Absar (Biocatalysis and Biotransformation, 2013)
A fungal transformation method for the production of the less abundant but more valuable anticancer drug vincristine using the more abundant anticancer drug vinblastine by an endophytic fungus Fusarium oxysporum isolated from the plant Catharanthus roseus is described. Vinblastine dissolved in sterile water when incubated with the fungal mycelial mass was transformed into vincristine at room temperature. The biotransformation process was monitored by periodic sampling of aliquots that were extracted with ethyl acetate. The crude transformed compounds were analysed using TLC where the Rf value of the spot obtained on the 8th day was found to be similar to that of standard vincristine (Rf 0.74). Purification by HPLC using a C 18 symmetry column showed a peak with RT (34.9 min) similar to that of standard vincristine. Further characterization with the help of ESI-MS showed a peak at m/z 825 attributed to the (M + H)(+) ion. This indicated that the fungus Fusarium oxysporum had converted vinblastine to vincristine.
Keywords: Biotransformation; endophytes; fusarium oxysporum; Vinblastine; vincristine

Isolation, purification and characterization of vinblastine and vincristine from endophytic fungus fusarium oxysporum isolated from catharanthus roseus - Kumar, Ashutosh; Patil, Deepak; Rajamohanan, Pattuparambil Ramanpillai; Ahmad, Absar (Plos One, 2013)
Endophytic fungi reside in a symbiotic fashion inside their host plants, mimic their chemistry and interestingly, produce the same natural products as their hosts and are thus being screened for the production of valuable compounds like taxol, camptothecin, podophyllotoxin, etc. Vinblastine and vincristine are excellent anti-cancer drugs but their current production using plants is non-abundant and expensive. In order to make these drugs readily available to the patients at affordable prices, we isolated the endophytic fungi from Catharanthus roseus plant and found a fungus AA-CRL-6 which produces vinblastine and vincristine in appreciable amounts. These drugs were purified by TLC and HPLC and characterized using UV-Vis spectroscopy, ESI-MS, MS/MS and H-1 NMR. One liter of culture filtrate yielded 76 mu g and 67 mu g of vinblastine and vincristine respectively. This endophytic fungal strain was identified as Fusarium oxysporum based upon its cultural and morphological characteristics and internal transcribed spacer (ITS) sequence analysis.